STRATEGI KOMUNIKASI KRISIS HUMAS PEMKAB NGANJUK DALAM PEMULIHAN CITRA PASCA KASUS KORUPSI - Widyastuti, Aritma; Ekoputro, Widiyatmo (Sintesa, 2023)
Government organizations, in crisis conditions, need and are very important to maintain their reputation so that their image in the eyes of the public is viewed favorably, so that public trust in them can recover and stabilize. The role of social media in the image of a government organization is as a bridge of information and control of information lanes that are closely related to the image itself. Instagram social media is one of the means of information that is currently favored by millennial people to obtain information. Therefore, by using qualitative methods, researchers describe how a positive image of a government organization is important and how to apply crisis communication using image restoration theory developed by Benoit (1995). By conducting a case study on Instagram @diskominfo_nganjuk researchers observed how the role of Diskominfo's Instagram social media played a role in implementing crisis communication strategies in handling the issue of corruption cases that occurred in 2021. This is also related to Diskominfo's mission in information disclosure from the government to the public is one of the important things to be achieved by the Communication and Information Service. One of them was realized by the Nganjuk Regency Communication and Information Office by disseminating information, namely through @dinaskominfo_nganjuk Instagram content with various themes and topics around Nganjuk Regency information with the aim of disseminating information to be able to reach all circles of society.